Development of a contouring guide for three different types of optic chiasm: A practical approach. Issue 5 (7th June 2019) - Chen, Wenhao; Zhang, Hui; Zhang, Wenyi; Su, Meng; Xie, Raoying; Li, Kejie; Xia, Xiaofang; Zou, Changlin
Abstract: Introduction: Sparing of the organs at risk (OARs) is a crucial task in daily radiotherapy practice. Irradiation of the optic chiasm (OC) results in radiation‐induced optic neuropathy (RION). The structure of the OC is complex, and OC morphology can vary in axial images. Therefore, a standard atlas can result in inaccurate descriptions of OC morphology in different patients. The aim of our study was to provide a guide based on computed tomography (CT) for the delineation of different types of OC. Methods: Thirty‐six patients were selected to participate in our study. These patients underwent CT analysis of the brain, head and neck regions in a supine position. Axial images 3 mm in thickness were obtained at 3‐mm intervals. A magnetic resonance imaging (MRI) study was also performed using the same set‐up. The OC was then delineated. The contours were revised by three neuroradiologists and nine radiation oncologists with > 5 years of expertise. Results: Three types of OC were distinguished by magnetic resonance (MR). The location and boundaries of normal, prefixed and postfixed chiasms were developed with a CT‐based atlas. Discrepancies were observed in the delineation of the prefixed and postfixed OC. Conclusions: Our guide allows improved definitions of the anatomical boundaries for different types of OC. Our experience could provide useful information for radiation oncologists in daily practice.